2018
DOI: 10.1016/j.peptides.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic discovery and comparative analysis of neuropeptide precursors in sea cucumbers (Holothuroidea)

Abstract: Neuropeptides synthesized and released by neuronal cells play important roles in the regulation of many processes, e.g. growth, feeding, reproduction, and behavior. In the past decade, next-generation sequencing technologies have helped to facilitate the identification of multiple neuropeptide genes in a variety of taxa, including arthropods, molluscs and echinoderms. In this study, we extend these studies to Holothuria scabra, a sea cucumber species that is widely cultured for human consumption. In silico ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 43 publications
(62 reference statements)
4
44
0
1
Order By: Relevance
“…Besides these similarities, there were clearly two types of peptides based on the spacing of the cysteine residues: with respect to the cleavage site, the CTa-types displayed the C9/8XC motif, while the CTb-types displayed the C7XC motif. The arrangement of the oyster CTPs with two mature peptides is particularly intriguing as deuterostome CT-type peptide precursors contain either a single peptide (Muff et al, 1995;Sekiguchi et al, 2009) or two peptides, as observed in echinoderm CT-type precursors (Rowe et al, 2014;Suwansa-ard et al, 2018;Zandawala et al, 2017). In the protostomes, the annelid P. dumerilii CT and DH31 precursors (Conzelmann et al, 2013) and the DH31 and CT-A precursors in arthropods (Alexander et al, 2018;Christie, 2008;Christie et al, 2010;Coast et al, 2001;Gard et al, 2009;Li et al, 2007;Veenstra, 2014 comprise only one peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these similarities, there were clearly two types of peptides based on the spacing of the cysteine residues: with respect to the cleavage site, the CTa-types displayed the C9/8XC motif, while the CTb-types displayed the C7XC motif. The arrangement of the oyster CTPs with two mature peptides is particularly intriguing as deuterostome CT-type peptide precursors contain either a single peptide (Muff et al, 1995;Sekiguchi et al, 2009) or two peptides, as observed in echinoderm CT-type precursors (Rowe et al, 2014;Suwansa-ard et al, 2018;Zandawala et al, 2017). In the protostomes, the annelid P. dumerilii CT and DH31 precursors (Conzelmann et al, 2013) and the DH31 and CT-A precursors in arthropods (Alexander et al, 2018;Christie, 2008;Christie et al, 2010;Coast et al, 2001;Gard et al, 2009;Li et al, 2007;Veenstra, 2014 comprise only one peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Through analysis of transcriptome/genome sequence data, luqin-type neuropeptide precursors have subsequently been identified in other echinoderm classes, including Holothuroidea (sea cucumbers), Asteroidea (starfish or sea stars), and Ophiuroidea (brittle stars). In the sea cucumbers Apostichopus japonicus, Holothuria glaberrima, Holothuria scabra, and Holothuria leucospilota, the precursor comprises a single neuropeptide with the same predicted structure in all four species-KPYKFMRW-NH 2 (Rowe et al, 2014;Suwansa-Ard et al, 2018;Chen et al, 2019;Chieu et al, 2019). Luqin-type precursors identified in the starfish species A. rubens and Acanthaster planci comprise a single putative neuropeptide with the amino acid sequence EKGRFPKFMRW-NH 2 and EEKTRFPKFMRW-NH 2 , respectively Smith et al, 2017).…”
Section: Discovery Of Luqin-type Signaling In Ambulacrarian Deuterostmentioning
confidence: 99%
“…Most transcriptomes were made from several whole adults and should thus include neuronal expression (see Supplementary Table 1 for details). To obtain reference and query sequences, we collected neuropeptide-precursor and neuropeptide receptor sequences from previous publications [1, 2, 54-60] and public databases (i.e., NCBI and UniProt). We aimed for a broad sampling across Bilateria and covered different clades of chordates (i.e., Craniata, Cephalochordata, and Urochordata), ambulacrarians (i.e, Echinodermata and Hemichordata) ecdysozoans (i.e., Nematoda and Arthropoda) and spiralians (i.e., Mollusca and Annelida).…”
Section: Methodsmentioning
confidence: 99%